Fuzzy Soft Min-Max Decision Making and its Applications (Journal of Informatics and Mathematical Sciences, 2017)
In this paper, we study fuzzy soft matrix and fuzzy soft max-min decision making method. Then we introduce a fuzzy soft min-max decision making method based on a respective decision making function and two more examples are given using the AND and OR products of fuzzy soft matrices.
Keywords: Bipolar fuzzy graph (BFG); Strong edge; Dominating set; Domination number; Global dominating set; Global domination number; Semi complete; Purely semi complete; Semi complementary; Semi global dominating set and semi global domination number